EFFECTIVENESS OF OSMOPROTECTANTS IN IMPROVING AROMA QUALITY AND YIELD OF PARE WANGI UPLAND RICE VARIETY GROWN ON TWO DIFFERENT SOIL TYPES IN EAST NUSA TENGGARA - I.G.B. Adwita Arsa; Ariffin Ariffin; Nurul Aini; H.J.D. Lalel (AGRIVITA, Journal of Agricultural Science, 2016)
This study aimed to evaluate the effectiveness of exogenous osmoprotectant application in increasing the stability of aroma quality and grain yield of Pare Wangi on different soil types. A two factors greenhouse experiment was designed according to Split Plot design with three replications. The first factor was soil types of specific and target location. The second factor was application of exogenous osmoprotectants, i.e. without osmoprotectant, 10 mM proline, 20 mM proline, 10 mM sorbitol, 20 mM sorbitol, 10 mM sucrose and 20 mM sucrose. Observed data included soil physical and chemical properties, rice vegetative and reproductive growth and physiological characters, and rice aroma quality. Collected data were subjected to analysis of variance, followed by an Honestly Significant Difference (HSD) post hoc and a simple correlation tests. Results indicated that grain yield per pot was higher on soil from target location than on soil from specific location, but concentration of proline and 2AP, and the aroma scores were in the opposite direction. Besides more effective in increasing grain yield, the osmoprotectants proline and sucrose, each at 10 mM, were also better in maintaining rice aroma quality compared tosorbitol osmoprotectants, and aroma score showed a significantly positive correlation with 2AP concentration.